Comparing myocardial perfusion scan findings in patients with and without Covid-19 - Bahar Moasses-Ghafari; Sahar Choupani; Sajed Jahanbin; Reza Lotfi; Khaled Rahmani (BMC Cardiovascular Disorders)
Abstract Background Covid-19 is a pandemic viral disease that directly or indirectly affects multiple organ systems, including the cardiovascular system. SPECT GATED MPI is a non-invasive nuclear imaging modality used to assess myocardial perfusion and function. The aim of this study was to evaluate the effect of Covid-19 pandemic on myocardial perfusion imaging in ischemic heart disease. Methods This was a cross-sectional (descriptive-analytical) study of 750 patients requiring myocardial perfusion imaging (MPI) who were referred to the nuclear medicine center of Kowsar Hospital, a teaching hospital in Sanandaj, the center of Kurdistan Province in north-western Iran. Data collection was performed during the Covid-19 pandemic, between 6 April 2020 and 21 March 2021. Data analysis was performed in SPSS using independent samples t-test and chi-squared. Results A total of 750 patients, including 328 (43.7%) Covid-19 positive and 422 (56.3%) Covid-19 negative, were included in the analysis. Although Covid-19 infected obese patients had a significantly higher rate of abnormal MPI (P < 0.0001), no significant difference in abnormal MPI was observed between the two groups (p = 0.551). Conclusion The lack of a significant difference in the incidence of abnormal MPI between the two groups suggests that there may be Covid-19 patients with potentially abnormal MPI who have gone undetected. In addition, Covid-19 patients with pleural chest pain, myalgia or dyspnea may have been misdiagnosed as having chest pain secondary to heart disease.